A Report of a Novel Pathogenic Variant in a Family with Buschke–Ollendorf Syndrome - Jain, Angita; Selvam, Pavalan; Atwal, Herjot; Atwal, Paldeep S. (Journal of Pediatric Genetics, 2020)
Buschke–Ollendorf Syndrome (BOS) is a benign autosomal dominant disorder caused by pathogenic mutations in LEMD3. Here, we describe a family diagnosed to have varied phenotypes associated with BOS. Single gene testing of LEMD3 detected a heterozygous frameshift pathogenic variant in both the affected family members. Besides the phenotypic description, this report highlights the need for a comprehensive evaluation in connective tissue disorders and the importance of genotype–phenotype correlation in BOS.
Keywords: familial Buschke–Ollendorf syndrome; osteopoikilosis; collagenoma; LEMD3